SPATIAL-TEMPORAL ANALYSIS OF JAKARTA RECLAMATION ISLANDS 2014-2024: A CASE STUDY OF ISLANDS C, D AND G - Hikmah, Nur; Wibowo, Adi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Reclamation projects in Jakarta Bay, particularly on Islands C, D and G, have brought significant changes to the structure of coastal areas over the past decade. This study aims to analyze the spatial-temporal changes of the three islands using Google Earth satellite image data from 2014, 2019 and 2024 processed with Geographic Information System (GIS) software. The results of the analysis showed that in 2014 only Island D began to form with an area of 267.44 hectares, while Islands C and G were not yet visible. In 2019, the area of Island C reached 114 hectares, Island D 324 hectares, and Island G 21.37 hectares. By 2024, the area of Island C increased to 134 hectares, Island D to 319.19 hectares, while Island G decreased in area to only 1.37 hectares. This reclamation impacts land cover patterns, with open land turning into built-up areas and loss of mangrove vegetation around the islands. Environmental impacts include increased sedimentation, water quality degradation and risk of tidal flooding. In addition, there is a mismatch between reclamation management and sustainable spatial principles stipulated in DKI Jakarta’s Regional Spatial Plan (RTRW). This research highlights the importance of more integrated and sustainable reclamation management. Recommendations include mangrove reforestation, reclamation waste management, and revision of spatial policies to support a balance between economic development and environmental conservation.